2020
DOI: 10.2147/jep.s260731
|View full text |Cite
|
Sign up to set email alerts
|

<p>Protective Effect of <em>Croton macrostachyus</em> (Euphorbiaceae) Stem Bark on Cyclophosphamide-Induced Nephrotoxicity in Rats</p>

Abstract: Background: Cyclophosphamide is an alkylating antineoplastic agent and its major limitation is injury to normal tissue, leading to multiple organ toxicity, including kidney, heart, liver and reproductive toxicity. Croton macrostachyus (Euphorbiaceae) has been used in Ethiopian traditional medicine to manage renal diseases. Objective: The present study aims to assess the protective effect of the stem bark extract and solvent fractions of Croton macrostachyus on cyclophosphamide-induced nephrotoxicity in rats. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The results from this study indicated that CTX significantly altered kidney function parameters as portrayed by elevated serum BUN, uric acid and creatinine. These results corroborated with previous studies indicating CTX mediated increase in serum renal toxicity markers [9,17] …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results from this study indicated that CTX significantly altered kidney function parameters as portrayed by elevated serum BUN, uric acid and creatinine. These results corroborated with previous studies indicating CTX mediated increase in serum renal toxicity markers [9,17] …”
Section: Discussionsupporting
confidence: 93%
“…These results corroborated with previous studies indicating CTX mediated increase in serum renal toxicity markers. [9,17] Several studies have indicated that increased concentration of serum creatinine, BUN and uric acid are indices of kidney damage which has been attributed to filtering of these biomarkers into the blood systemic circulation. [6,18] These typical biochemical parameters of kidney damage were amplified and confirmed by renal histopathological alterations including interstitial haemorrhage, degeneration of the glomerulus and renal atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…It also protects against toxicity of different organs including kidney [25][26] , liver [27] , and hurt [28] . CP-induced nephrotoxicity in rats [25,[29][30] , and in mice [31][32][33] have been reported. In rats, tubular epithelial degeneration [34] collagen bundles around vessels, tubules and also in glomeruli [29] , inflammatory cells infiltration, tubular necrosis [30] and glomerular necrosis [25] have been reported in kidneys of CP given animals.…”
Section: Discussionmentioning
confidence: 99%
“…CP-induced nephrotoxicity in rats [25,[29][30] , and in mice [31][32][33] have been reported. In rats, tubular epithelial degeneration [34] collagen bundles around vessels, tubules and also in glomeruli [29] , inflammatory cells infiltration, tubular necrosis [30] and glomerular necrosis [25] have been reported in kidneys of CP given animals. In mice, degeneration [31][32][33] , swelling [31][32] necrosis and congestion [32] , casts formation and atrophy [33] in tubuli and thickened basal membrane, widened Bowman's space [33] , degeneration [31,33] , atrophy [33] in glomeruli, and also inflammatory cells infiltration in cortical and medullary area [32][33] have been evaluated in CP-induced renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, the therapeutic use of CP is restricted due to the side effects it produces, such as nephrotoxicity, cardiotoxicity, and hepatotoxicity [3]. Renal damage induced by CP includes apoptosis and necrosis of tubular epithelial cells [3], inflammation [4], fibrosis [5], and decreased lysosomal enzyme activity [6]. The toxic mechanism of CP is attributed to its main metabolites, phosphoramide mustard and acrolein, which cause an increase in free radicals [7].…”
Section: Introductionmentioning
confidence: 99%